2014
DOI: 10.2166/wh.2014.217
|View full text |Cite
|
Sign up to set email alerts
|

Minimum inhibitory concentration distribution in environmental Legionella spp. isolates

Abstract: In Greece standard tests are performed in the watering and cooling systems of hotels' units either as part of the surveillance scheme or following human infection. The purpose of this study was to establish the minimum inhibitory concentration (MIC) distributions of environmental Legionella isolates for six antimicrobials commonly used for the treatment of Legionella infections, by MIC-test methodology. Water samples were collected from 2004 to 2011 from 124 hotels from the four prefectures of Crete (Greece). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…In another Italian study [ 41 ], the authors revealed that rifampicin was the most active antibiotic followed by levofloxacin, tigecycline and doxycycline. These results coincide with the results of previous studies [ 28 , 29 , 38 , 42 , 43 , 44 ]. Furthermore, all the Legionella strains were inhibited by low concentrations of macrolides and fluoroquinolones, while between the macrolides, clarithromycin was, overall, the most active drug compared to azithromycin.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In another Italian study [ 41 ], the authors revealed that rifampicin was the most active antibiotic followed by levofloxacin, tigecycline and doxycycline. These results coincide with the results of previous studies [ 28 , 29 , 38 , 42 , 43 , 44 ]. Furthermore, all the Legionella strains were inhibited by low concentrations of macrolides and fluoroquinolones, while between the macrolides, clarithromycin was, overall, the most active drug compared to azithromycin.…”
Section: Resultssupporting
confidence: 93%
“…In deciding which antibiotics should be selected to work with, the following criteria were considered: (a) the most cited antibiotics in the revised articles included in the study ( Table S1 raw data), (b) the guidelines of the Sanford Guide to Antimicrobial Therapy [ 24 ], and (c) the antibiotics administered in Greece [ 25 , 26 , 27 , 28 ]. This process resulted in the inclusion of seven (7) antibiotics in the search, these being ciprofloxacin (CIP), erythromycin (ERM), azithromycin (AZM), doxycycline (DOX), levofloxacin (LEV), rifampicin (RIF) and clarithromycin (CL).…”
Section: Methodsmentioning
confidence: 99%
“…It should be noticed however, that it turns out that it not just the presence of a WSP that will ensure the diminishing of the danger for a human infection by water-borne pathogens (including Legionella ); its proper implementation is sometimes a more crucial factor [ 45 ]. In fact, it is possible that the improper implementation or the complete absence of a WSP (leading sometimes to temperature and pH values out of range) may provide the ideal stress conditions for the Legionella bacteria to develop a decreased sensitivity to antibiotics [ 46 ]. Of course, this is a huge aspect that needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The MIC and MBC of tea polyphenols against H. parasuis were determined as previously described [ 9 , 20 ]. The MIC of tea polyphenols was defined as the minimum concentration at which no bacterial growth can be observed.…”
Section: Methodsmentioning
confidence: 99%